Manajemen program short courses - Nora Saiva Jannana; Yoyon Suryono (Jurnal Akuntabilitas Manajemen Pendidikan, 2017)
Penelitian ini bertujuan mendeskripsikan manajemen, faktor pendukung, faktor penghambat, dan solusi yang dilakukan pengelola untuk mengatasi penghambat program short courses di Alfabank Yogyakarta. Penelitian ini adalah penelitian studi kasus dengan pendekatan kualitatif. Pengumpulan data dilakukan dengan wawancara, observasi, dan dokumentasi. Analisis data menggunakan teknik analisis model interaktif Miles Huberman. Hasil penelitian: (1) Program short courses diselenggarakan guna memenuhi dengan segera kebutuhan tenaga kerja bidang komputer perbankan. Manajemen program short courses terdiri atas tahapan: pengkajian/analisis kebutuhan, perancangan, pelaksanaan, dan evaluasi program short courses. (2) Faktor pendukung: motivasi pengelola, ada job description, kebutuhan masyarakat, lulusan yang diakui, kenyamanan peserta, dan materi kursus relevan. (3) Faktor penghambat: RPP belum lengkap, pelayanan informasi terlambat, gangguan pemadaman listrik, keterbatasan pemakaian kelas, pelaksanaan kursus tidak sesuai jadwal, dan perbedaan daya tangkap peserta kursus. (4) Solusi: membentuk tim penyusun administrasi pembelajaran, menyediakan hotline service, segera bertindak atas keluhan modifikasi hardware, dan pengulangan materi kursus.Kata kunci: manajemen program, program short courses, pendidikan nonformal MANAGEMENT OF SHORT COURSE PROGRAMSAbstractThis studi aims to describe the management, find the supporting, obstacles, and solutions conducted by manager to overcome the obstacles in the management short course programs in Alfabank Yogyakarta. This research is a case study with the qualitative approach. The data were collected through interviews, observation, and documentation. The data analysis used the data analysis of Miles Huberman interactive model techniques. The results: (1) The short course programs organized to meet the immediate needs of workers in computer and banking field. The management of the short course programs consists of: needs analysis, design, implementation, and evaluation of the short course programs. (2) The supporting factors: motivation of resourse institution, the clarity of job description, the community needs, the output of Alfabank which is recognized, the comfort of course participants, and the relevant of course materials. (3) The obstacles: lesson plan  which cannot be completed, the delay of information services, the power outages, the limited use of classrooms, the implementation of short courses not according to the schedule, and the different ability of course participants. (4) The solutions: the administration of learning was created by team, the hotline services was prepared, the damage was directly checked and hardware modification by manager, and the course materials was repeated.Keywords: program management, short course programs, nonformal education